Extracorporeal Life Support for Respiratory Failure in Patients With Electronic Cigarette or Vaping Product Use–Associated Lung Injury. Issue 2 (15th September 2021) - Gupta, Vikas S.; Hayes, Don; Hsu, Stephanie C.; Tonna, Joseph E.; Rycus, Peter T.; Bridges, Brian C.; Diaban, Fatima; Bosma, Karen J.; Bhatt, Jayesh M.; Sakla, Nicole M.; Han, Jason J.; Bermudez, Christian A.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Electronic cigarette or vaping product use–associated lung injury is a clinical entity that can lead to respiratory failure and death. Despite the severity of electronic cigarette or vaping product use–associated lung injury, the role of extracorporeal life support in its management remains unclear. Our objective was to describe the clinical characteristics and outcomes of patients with electronic cigarette or vaping product use–associated lung injury who received extracorporeal life support. DESIGN: We performed a retrospective review of records of electronic cigarette or vaping product use–associated lung injury patients who received extracorporeal life support. Standardized data were collected via direct contact with extracorporeal life support centers. Data regarding presentation, ventilatory management, extracorporeal life support details, and outcome were analyzed. SETTING: This was a multi-institutional, international case series with patients from 10 different institutions in three different countries. PATIENTS: Patients who met criteria for confirmed electronic cigarette or vaping product use–associated lung injury (based on previously reported diagnostic criteria) and were placed on extracorporeal life support were included. Patients were identified via literature review and by direct contact with extracorporeal life support centers. MEASUREMENTS AND MAIN RESULTS: Data were collected for 14 patients ranging from 16 to 45 years old. All had confirmed vape use within 3 months of presentation. Nicotine was the most commonly used vaping product. All patients had respiratory symptoms and radiographic evidence of bilateral pulmonary opacities. IV antibiotics and corticosteroids were universally initiated. Patients were intubated for 1.9 days (range, 0–6) prior to extracorporeal life support initiation. Poor oxygenation and ventilation were the most common indications for extracorporeal life support. Five patients showed evidence of ventricular dysfunction on echocardiography. Thirteen patients (93%) were placed on venovenous extracorporeal life support, and one patient required multiple rounds of extracorporeal life support. Total extracorporeal life support duration ranged from 2 to 37 days. Thirteen patients survived to hospital discharge; one patient died of septic shock. CONCLUSIONS: Electronic cigarette or vaping product use–associated lung injury can cause refractory respiratory failure and hypoxemia. These data suggest that venovenous extracorporeal life support can be an effective treatment option for profound, refractory respiratory failure secondary to electronic cigarette or vaping product use–associated lung injury.